Workers' perceptions on the tolerability of their respirators in Malaysia - Yusof, Muhammad Zubir; Mukhtar, Nor Izzah (Emerald Publishing, 2023)
Background: Little is known about Malaysian workers' tolerance for respirators in the workplace. This study aimed to assess Malaysian workers' perceptions of respirator tolerability and its relationship to socio-demographics and compliance.